Western Australian students' alcohol consumption and expenditure intentions for Schoolies - Jongenelis, Michelle; Pettigrew, Simone; Biagioni, Nicole; Hagger, Martin (C S I R O Publishing, 2016)
In Australia, the immediate post-school period (known as 'Schoolies') is associated with heavy drinking and high levels of alcohol-related harm. This study investigated students' intended alcohol consumption during Schoolies to inform interventions to reduce alcohol-related harm among this group. An online survey was administered to students in their senior year of schooling. Included items related to intended daily alcohol consumption during Schoolies, amount of money intended to be spent on alcohol over the Schoolies period, and past drinking behaviour. On average, participants (n=187) anticipated that they would consume eight standard drinks per day, which is substantially higher than the recommended maximum of no more than four drinks on a single occasion. Participants intended to spend an average of A$131 on alcohol over the Schoolies period. Although higher than national guidelines, intended alcohol consumption was considerably lower than has been previously documented during Schoolies events. The substantial amounts of money expected to be spent during Schoolies suggest this group has adequate spending power to constitute an attractive target market for those offering alternative activities that are associated with lower levels of alcohol-related harm.